2015
DOI: 10.1021/acs.orglett.5b00728
|View full text |Cite
|
Sign up to set email alerts
|

C–H Bonds Phosphorylation of Ketene Dithioacetals

Abstract: C-H bond phosphorylation of ketene dithioacetals was achieved under transition-metal-free or AgNO3 mediated conditions. Synthetic transformations of the coupling product provided promising methods for the construction of highly functionalized phosphorylated N-heterocycles and tetrasubstituted alkenes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 63 publications
0
31
0
Order By: Relevance
“…For instance, Li, Wang and co-workers described a closely related concept based on C-H activation reaction instead of the insertion of the palladium in the aryl halide bond. (Scheme 30) [44] In this reaction, acetamides serves as an orthodirecting group for the palladium insertion. Then, thanks to a Pd II /Pd III /Pd IV cycle, the ortho-carbonylation is possible on several acetamides 189 in good yields.…”
Section: Carbonylation Reactionsmentioning
confidence: 99%
“…For instance, Li, Wang and co-workers described a closely related concept based on C-H activation reaction instead of the insertion of the palladium in the aryl halide bond. (Scheme 30) [44] In this reaction, acetamides serves as an orthodirecting group for the palladium insertion. Then, thanks to a Pd II /Pd III /Pd IV cycle, the ortho-carbonylation is possible on several acetamides 189 in good yields.…”
Section: Carbonylation Reactionsmentioning
confidence: 99%
“…Li, Wang et al reported decarboxylative o-acylation of acetanilides with α-oxocarboxylic acids as an acyl radical source (Scheme 62). [246] Eosin Y (3 mol-%) was used for photo-oxidation of α-oxocarboxylic, and O 2 as sacrificial oxidant. The presence of an amide-directing group in combination with Pd(OAc) 2 allowed the ortho-C-H activation of the aryl substrate.…”
Section: Strategymentioning
confidence: 99%
“…24 Interestingly, with secondary phosphine oxides, this transformation could take place with 3 equiv K 2 S 2 O 8 as the oxidant, whereas 3 equiv AgNO 3 were required with Hphosphonates. 24 Interestingly, with secondary phosphine oxides, this transformation could take place with 3 equiv K 2 S 2 O 8 as the oxidant, whereas 3 equiv AgNO 3 were required with Hphosphonates.…”
Section: Constructing Sp 2 C-p Bondsmentioning
confidence: 99%